Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Ahass Daya Motor - Faturachman Pramudya; Suroso; Maman Mulya Karnama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine whether work discipline and motivation simultaneously or partially affect the performance of employees at PT. Ahass Daya Motor. This research uses a quantitative methodology. The study was conducted at PT. Ahass Daya. The sample for this study consisted of 36 employees of PT. Ahass Daya Motor. Saturated sampling is the approach used for sample collection in this study. Meanwhile, the analysis used is the multiple linear regression model with F and T tests using a significance level of 5%. The results of the study indicate a partial relationship between the T table value (3.172 > 2.034, T calculated > T table) and employee work motivation. Work discipline partially affects employee performance, as indicated by the T table (2.397 > 2.034). Referring to the results of the study, the factors of motivation and work discipline have an impact on the performance of employees at PT. Ahass Daya Motor.